Paediatric Cerebral Sinovenous Thrombosis: Diagnostic challenges, therapeutic uncertainties, and context-sensitive management opportunities - Shazia K. Lashari; Mubeen F. Rafay (Journal of the Pakistan Medical Association, 2026)
Cerebral sinovenous thrombosis (CSVT) constitutes a relatively smaller, but clinically significant and disproportionately morbid cause of childhood cerebrovascular disease. The annual incidence of cerebral sinovenous thrombosis in children (term neonates through 18 years) ranges between 0.4 and 0.7 per 100,000 children per year and is relatively more common in neonates compared with older children.1 CSVT is often associated with cerebral venous infarction (ischaemia or haemorrhage or both) and increase in intracranial pressure, leading often to significant long-term neurodevelopmental impairment, epilepsy and even death.2 Considering paediatric arterial ischaemic stroke (AIS) the predominant subtype of paediatric stroke, CSVT remains relatively underexplored across both highincome and resource-limited healthcare settings, resulting in persistent diagnostic and therapeutic gaps. These gaps are particularly consequential in resourcelimited low- and middle-income countries (LMICs), frequently resulting in delayed recognition of CSVT and preventable neurological sequelae.3-5